2011
DOI: 10.1017/s0332586512000030
|View full text |Cite
|
Sign up to set email alerts
|

Token-reflexive, anaphoric and deictic functions of ‘here’

Abstract: There are basically three ways in which the reference of a token of the English proximal spatial indexicalhereand corresponding terms in other languages can be resolved in the context-dependent, pragmatic phase of the addressee's determination of the propositional content of an utterance that contains this adverbial adjunct. ‘Here’ may refer reflexively to the place of utterance, including minimally the spot occupied by the speaker (token-reflexive reference), it may be anaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Liver metastases was verified in one patient (case 14). Ascites of varying degree occurred in seven patients (cases [13][14][15][16][17][18][19]. One patient (case 14) had virtually complete stenosis of the gastric antrum, due to the cancer, and one patient (case 10) with a recurrent scirrhous carcinoma in the cardia region had almost complete stenosis of the cardia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver metastases was verified in one patient (case 14). Ascites of varying degree occurred in seven patients (cases [13][14][15][16][17][18][19]. One patient (case 14) had virtually complete stenosis of the gastric antrum, due to the cancer, and one patient (case 10) with a recurrent scirrhous carcinoma in the cardia region had almost complete stenosis of the cardia.…”
Section: Methodsmentioning
confidence: 99%
“…In cancer of the stomach Fretheim (1954Fretheim ( , 1955 has found that the blood volume is slightly reduced, mainly as a result of a reduced red-cell volume, but that the plasma volume is normal or only slightly reduced (referred to "ideal weight"). In cases of marked anaemia he reported a slightly increased plasma volume, probably a compensatory mechanism.…”
Section: Blood Plasma and Red-cell Volumesmentioning
confidence: 99%